Sistema aquapônico como alternativa agroecológica para a produção sustentável e integrada de alimentos: um estudo de caso em uma unidade de produção familiar em Tauerá de Beja, Abaetetuba-Pa - REIS, Maria Fatiane Araújo (2023)
The objective was to implement and evaluate an Aquaponics System for intercropped production of fish and vegetables in a Family Production Unit in Tauerá de Beja, rural area of Abaetetuba, Pará. The system was implemented on the property in February 2022 and had three main components: a 1000 liter water tank for raising fish, a wooden bench for producing vegetables in a gravel growing environment, and finally, a filtering set to purify the system, consisting of a decanter bucket and a filter bucket. The materials used in the assembly were, for the most part, reused and purchased from the family farm itself. Initially, the system proposal focused on the production of 50 tilapia (Oreochromis niloticus) intercropped with the cultivation of three vegetable species: lettuce (Lactuca sativa L.), sweet pepper (Capsicum annuum L.) and tomato (Solanum lycopersicum L.). However, it was found that the lack of oxygenation, caused by irregularity in the supply of electricity, was a critical point faced during the initial four months of the experiment, resulting in the mortality of most of the stored animals. For this reason, aiming at proper functioning and success in production, the system had to be resized, that is, it was necessary to change plant and animal species and reduce the number of fish produced in the system. Thus, in the next phase, twenty-five fish of the tambacu species (Colossoma macropomum x Piaractus mesopotamicus) were placed in the breeding tank and twenty-seven vegetables were grown on the vegetable bench, including 12 chicory seedlings (Cichorium intybus L.), 10 of cabbage (Brassica oleracea L.) and five of mint (Mentha spicata L.). Every 15 days, a biometric evaluation and water quality control were carried out to verify the parameters of dissolved oxygen, pH, nitrite and ammonia content. Due to the growth of the animals, it was necessary to include another submersible pump for the aquarium in the system, to increase the availability of oxygen in the fish water. After the modification, the fish and vegetables inserted in the system performed well, with special emphasis on mint, which propagated easily on the hydroponic bench. It is concluded, therefore, that the instability in the supply of electricity was a limiting factor in the performance of the aquaponic system for the case under study (property in a rural community in the Amazon), and that, therefore, if the system could be implanted in the rural area, there is a need to reduce production, especially of fish, so that this type of system can be used as an alternative tool for the production of agroecological foods in the municipality of Abaetetuba.